Building a Plane While Flying - Beyhan Farhadi; Sue Winton (University of Windsor, 2021)
We use the metaphor of building a plane while flying to describe the enactment of educational policies by teachers during COVID-19 and the impact of these policies on their ability to meet the needs of their students. Drawing from a series of three one-hour focus groups with seven teachers in Alberta, we apply critical policy analysis to describe the transition of public schools to pandemic education, especially in urban centers. This paper will begin by reviewing the dynamic policy context of school closures and reentry strategies and proceed to outline the diverse ways school boards interpreted guidelines from the Ministry of Education. We discuss the frustration with and variation of policy enactment during the pandemic, especially with respect to priorities and barriers to addressing student wellbeing and access to educational and social supports. Finally, we describe the consequences of teaching through crisis as it emerges in a political context that has failed to respond to educator's professional needs.